Historical sociology and its impact on international relations. - Ali Mohammed Idan (Tikrit Journal For Political Science, 2023)
The challenges facing historical social studies in international relations are multifaceted and have different aspects. As the relationship between the science of social history and the science of international relations is deep, intertwined and interdependent because it relates to the history of societies and their social characteristics that determines its identity, lifestyle, and relationship with its peers from other societies. Therefore, the role that historical sociology plays in serving researchers in the field of international relations is essential. Most international relation theories are based on it. Also, the relationship of historical sociology with theories of international relations helps to understand generalizations in the field of international relations. It contributed to its interpretation, analysis and testing throughout history, in addition to the contribution of the science of social history in revealing the laws that control the conduct of events that societies go through during a certain period of time. Through research and analysis, it was found that historical sociology has a positive impact on international relations. By providing research material for specialists in this field, the interdependence and overlap between the social sciences makes it difficult to distinguish the boundaries and breaks between them. It also provides ample room for specialists in this field to cooperate with each other.